Analysis of existing voting systems - Богдан, Юлия Игоревна; Веселая, Ольга Олеговна (Eastern-European Journal of Enterprise Technologies, 2012)
In the article was provided an overview and classification of existing e-voting systems (U.S., Estonia, Kazakhstan, Russia and others). Identified strengths and weaknesses ofsystems